THE EFFECTS OF PERGA SPORT CONTAINING PERGA (BEE BREAD) ON PERFORMANCE AND QUALITY OF LIFE IN SPORTERS FROM THE DIFFERENT SPORT DISCIPLINES AND SEDENTERS - Erdal Zorba; Mehmet Rüştü Karaman; Süleyman Gönülateş; Merve Karaman (ümit doğan üstün, 2019)
In this study, the effects of perga sport containing perga (bee bread) on performance and quality of life in sporters from different sport disciplines (Kick-Boks, Fitness, Karate, Atletizm) and sedenters were investigated. Perga Sport is a natural food having raw honey, pure perga, pollen and royal jelly mixture, which was especially developed for athletes and those with high daily energy needs. Perga sport; it is a superior food, due to its extremely rich composition and high bioactive availability, it is also a unique source of natural performance and energy. In the study, the data obtained after the measurements (right paw force, left paw force, back force, leg strength, lactate levels, shuttle numbers) applied to the participants before and after using Perga Sport were evaluated statistically. In order to determine the difference between the groups after the pre-test and post-test, the tests to be performed with parametric or non-parametric tests were used to determine the normal distribution of the data. According to the results of the research, as a result of the regular Perga Sport consumption of both athletes and sedentaries daily, all performance values (right paw force, left paw force, back force, leg strength, lactate levels, shuttle numbers, etc.) were significant (average 10-15% in athletes; 35-45% increase in sedentaries), and this increase has been scientifically proven to contribute significantly to athlete performance and quality of life of sedentaries.